2018
DOI: 10.1186/s12870-018-1240-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression of two barley proteinase inhibitors in tomato promotes endogenous defensive response and enhances resistance to Tuta absoluta

Abstract: BackgroundPlants and insects have coexisted for million years and evolved a set of interactions which affect both organisms at different levels. Plants have developed various morphological and biochemical adaptations to cope with herbivores attacks. However, Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) has become the major pest threatening tomato crops worldwide and without the appropriated management it can cause production losses between 80 to 100%.ResultsThe aim of this study was to investigate the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 85 publications
3
28
0
1
Order By: Relevance
“…These results are in accordance to some previous works indicating the detrimental effects of exogenous applications of different elicitor molecules such as benzothiadiazole (BTH), JA, and methyl jasmonate (MJ) on the fitness traits and population growth of aphids [34,35]. Nevertheless, some studies have shown how elicitors induce resistance against different sucking and chewing insect pests by the use of co-expression of different proteinase inhibitors [33,36,37]. Likewise, the exogenous treatment of different plant defense related proteins such as polyphenol oxidase and Pathogens 2020, 9, 111 7 of 13 proteinase inhibitors have been shown to significantly reduce the incidence of insect pests on tomato plants [34,38].…”
Section: Discussionsupporting
confidence: 92%
“…These results are in accordance to some previous works indicating the detrimental effects of exogenous applications of different elicitor molecules such as benzothiadiazole (BTH), JA, and methyl jasmonate (MJ) on the fitness traits and population growth of aphids [34,35]. Nevertheless, some studies have shown how elicitors induce resistance against different sucking and chewing insect pests by the use of co-expression of different proteinase inhibitors [33,36,37]. Likewise, the exogenous treatment of different plant defense related proteins such as polyphenol oxidase and Pathogens 2020, 9, 111 7 of 13 proteinase inhibitors have been shown to significantly reduce the incidence of insect pests on tomato plants [34,38].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, upregulation of defenses in leaves such as PIs and chitinases has also been reported in ectomycorrhizal poplar (Populus x canescens (Aiton)) damaged by the poplar leaf beetle (Chrysomela populi L.) [56]. It was shown recently that co-expression of the barley serine and cysteine PIs in tomato plants resulted in increased host resistance to the South American tomato pinworm Tuta absoluta (Meyrick) [57]. In this study, gene expression patterns were distinguished by measuring transcript levels in local and systemic leaves, indicating that priming by AM fungal colonization of roots may be more targeted to local tissues attacked by aphids.…”
Section: Discussionmentioning
confidence: 92%
“…Nevertheless, relatively little is known about the effects of JA-or SA-mediated plant responses on their performance and behavior. The expression of proteinase inhibitors, known to be induced by wounding, was recently shown not to affect the development and survival of N. tenuis in barley (Hamza et al, 2018). On the other hand, Podisus maculiventris preferred jasmonate-insensitive plants and their survival was higher on these compared to jasmonate-overexpressing plants (Thaler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%